Metaanálisis de transcriptomas de maíz (Zea Mays L.) en respuesta a fusarium verticillioides, f. graminearum y ustilago maydis - Peñas Ballesteros, Andrea (2022)
Maize (Zea mays L.) ears are affected by several pathogens that impact grain yield and quality, such as Fusarium verticillioides (necrotroph), F. graminearum (hemibiotroph) and Ustilago maydis (biotroph). Even though there is a large volume of transcriptomic data available at NCBI regarding maize responses to these pathogens, studies on multiple disease resistance are lacking. In this work, we aimed at identifying key genes and metabolic pathways involved in the multiple disease response of maize against the aforementioned ear rot pathogens. We analyzed RNA-seq data from four transcriptomic studies that evaluated resistant and/vs. susceptible maize genotypes under artificial inoculation at 48 and 72 hours after infection with each pathogen. The results obtained showed that resistant genotypes differentially overexpressed 1539 genes involved in the biosynthesis of phenylpropanoids, monoterpenoids and other secondary metabolites, while the susceptible genotypes differentially overexpressed 1356 genes associated with the photosynthesis pathway. This finding highlights that resistance leads to changes in secondary metabolism (specialized metabolites) based on the induction of defense programs while susceptibility leads to changes in primary metabolism which affect growth and development of the plant. These results will contribute towards our understanding of the mechanisms underlying multiple disease resistance to maize ear rot pathogens with different lifestyles.